Knowledge level of the Society about Fear of Missing Out Through Webinar in COVID-19 Pandemic - Prasetyo, Hersati; Putu Agus Arsana, I; Dewi Tri Utami, Mahrumi; Nur Indiastuti, Danti (Rifa'Institute, 2022)
The COVID-19 pandemic situation causes many people to be confined at home and triggers people to tend to spend more time accessing social media. Social media basically shows activities carried out by other people and this can trigger the phenomenon of Fear of Missing Out (FoMO). The purpose of this study is to know the level of knowledge of the Indonesian society about the FoMO and how to overcome it in the era of the COVID-19 pandemic. This study is a type of descriptive survey study; it describes the level of society knowledge about FoMO through webinars during the COVID-19 pandemic. The sample is 779 people who have met the inclusion and exclusion criteria. The data was obtained through a google form which was distributed to webinar participants, then processed and described in the form of a distribution table of respondents along with the average post-test results on a scale of 7 and 100 for the age group. The collected data were 779 respondents from different age groups (12-55 years). All existing age groups can answer more than half of the questions correctly. The average of questions answered correctly was almost the same in all age groups, with the 41–45-year-old group being in the top position. The average post-test result from all age ranges was 69.57. The average level of society knowledge about the FoMO phenomenon and how to solve it through webinar in the COVID-19 pandemic which was known from the post-test scores did not show much different results between each age range. This shows that all age ranges have the same susceptibility to experiencing FoMO.